The Semi-Quantitative Study of Magnetization Process on Milling and Reannealing of Barium Hexaferrite (BaO.6Fe2O3) - Ridwan Ridwan; Mujamilah Mujamilah; A. Johan (Atom Indonesia, 2009)
Barium hexaferrite (BaO.6Fe2O3) is as a hard magnetic material with good chemical stability which has been intensively used as permanent magnet components. Many works have been done in order to improve their magnetic properties either through chemical process or powders metallurgy technique. In this work, commercial BaO.6Fe2O3 was milled using high-energy milling machine for 10, 20 and 30 hours and followed by reannealing for 3 hours at 1000⁰C in air. X-ray diffraction pattern indicate no phase decomposition occurred caused the mill processing, annealing of milled powders recovered the crystal system and promoted crystallite growth. The magnetic hysteresis curve measured by vibrating sample magnetometer (VSM) shows the coercivity of annealed BaO.6Fe2O3 increases to two times higher than the original one. By using Jiles-Atherton model, all the hysteresis parameters Ms, k, α, a and c, have been determined adopted to the Genetic Algorithm (GA). The analyzed hysteretic parameters obtained from this work is congruent to the change of magnetic properties of as-milled and annealed powders of barium hexaferrite.Received: 16 February 2009; Revised: 1 September 2009; Accepted: 23 November 2009